EDUCATION IMPROVES KNOWLEDGE OF UTILIZING DIGITAL MARKETING FOR PRODUCT MARKETING FOR STUDENTS OF SMK 10 PADANG - Rahmania, Meri; Wati, Wati; Areva, Desi; Susanti, Nora (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
In today's digital era, the ability to adapt to technology is very important. One of the skills that are increasingly needed is digital marketing. Knowledge of Digital Marketing is part of Entrepreneurship Knowledge, which is one of the most important knowledge to be possessed by high school or vocational students. This activity is directed to students of SMK Negeri 10 Padang, because Entrepreneurship Education is already known to high school and vocational students through Creative Products and Entrepreneurship (PKKwu) subjects. The purpose of this community service is to provide education and assistance so that students can utilize and optimize digital marketing, especially through social media such as Instagram. The methods used in this service include material delivery and direct assistance. As a result of this activity, the participants successfully understood marketing strategies through Instagram. In addition, through this training, they gained knowledge on how to maximize the use of social media, including how to create simple content, set upload schedules, and establish good communication with consumers.